Happiness: Is it Prevalent amongst Students of Higher Educational Institutions? - Devvrat Singh, Anjali; Kaur Gujral, Harminder (International Journal of Psychosocial Rehabilitation, 2019)
The present research contributes to assessing happiness level of students of higher Educational Institutions through statistical analysis of factors such as academic years and gender, and proposing a model for „skills to remain happy‟. The study aims to expand the domain towards the well-being of future employees which ultimately leads to organizational effectiveness. The paper is based on an exploratory study using the survey approach through questionnaire. The sample size is 402 students from three academic years of Higher Educational Institution. The data has been complemented with documentary analysis, including behavioral science studies and research methods used therein. The paper provides empirical insights on the prevailing happiness level amongst University students. It provides an insight for future research dealing with questions like “Can Happiness be induced, taught or altered”, and if yes, for how long, and its overall effect on organizational effectiveness. The paper includes inferences for the organization‟s psychological contract with its employees and will thus be able to take care of the wellbeing of the employees, resulting in happiness. This may lead to compatible bond between employees and organization culminating in a better in-out ratio and increased level of trust and stability. This paper suffices recognized need to study how happiness can enhance organizational effectiveness.